The Impact of International Migration Process and Contemporary Trends in Kyrgyzstan - Sagynbekova, Lira (Springer International Publishing : Imprint: Springer, 2016)
This book comprises the historical overview of migration processes in Kyrgyzstan, contemporary migration trends in international migration and various social, economic and political impacts of migration. It presents the findings of longstanding, in-depth, comprehensive and empirical research. Insights are maximized by applying the multi-sited strategy of analyzing both the migrant's place of origin and that of destination. The primary goal of the book is to contribute to a better understanding of the meanings and the impacts of contemporary international migration processes in Kyrgyzstan and their relevance for local livelihoods.